25 Molecules Expressed in the AMPK Pathway After Exercise in Type 2 Diabetes: Evidence Map - Raquel da Franca; Andrea Penha Santana; Apolo Anunciação dos Santos Evangelista; Tamara dos Santos Lima; Dyandra Fernanda Lima de Oliveira; Jorge Luiz de Brito-Gomes; Ferdinando Oliveira Carvalho (Brazilian Archives of Biology and Technology)
ABSTRACT This study investigates the expression of molecules in the AMPK pathway following physical exercise in people with type 2 diabetes, considering aerobic, resistance, and combined exercises. Although the literature indicates intracellular signaling in the AMP-activated protein kinase (AMPK) pathway occurs after exercise, it is essential to compile this information to support clinical decision-making. To summarize evidence on the expression of molecules in the AMPK pathway in people with type 2 diabetes following aerobic, resistance, and combined exercise. This integrative review included searches in MEDLINE/PubMed, SciELO, and Lilacs databases (2004-2024). After applying filters, duplicate evaluations, and screening titles and abstracts, nine studies met the eligibility criteria. An increase in the expression of 25 molecules, particularly GLUT4 and PGC1-α, was observed, with combined exercise proving more effective than aerobic and resistance exercises alone. Aerobic, resistance, and combined exercises can increase the expression of molecules in the AMPK pathway in people with type 2 diabetes, with combined exercise being the most effective. There are differences not only between exercise types but also in volume, intensity, and frequency.